Physical Activity and Sedentary Behavior in Metabolically Healthy versus Unhealthy Obese and Non-Obese Individuals - The Maastricht Study. - Belle H de Rooij; Julianne D van der Berg; Carla J H van der Kallen; Miranda T Schram; Hans H C M Savelberg; Nicolaas C Schaper; Pieter C Dagnelie; Ronald M A Henry; Abraham A Kroon; Coen D A Stehouwer; Annemarie Koster (PLoS ONE, 2016)
BACKGROUND:Both obesity and the metabolic syndrome are associated with increased risk of cardiovascular diseases and type 2 diabetes. Although both frequently occur together in the same individual, obesity and the metabolic syndrome can also develop independently from each other. The (patho)physiology of "metabolically healthy obese" (i.e. obese without metabolic syndrome) and "metabolically unhealthy non-obese" phenotypes (i.e. non-obese with metabolic syndrome) is not fully understood, but physical activity and sedentary behavior may play a role. OBJECTIVE:To examine objectively measured physical activity and sedentary behavior across four groups: I) "metabolically healthy obese" (MHO); II) "metabolically unhealthy obese" (MUO); III)"metabolically healthy non-obese" (MHNO); and IV) "metabolically unhealthy non-obese" (MUNO). METHODS:Data were available from 2,449 men and women aged 40-75 years who participated in The Maastricht Study from 2010 to 2013. Participants were classified into the four groups according to obesity (BMI≥30kg/m2) and metabolic syndrome (ATPIII definition). Daily activity was measured for 7 days with the activPAL physical activity monitor and classified as time spent sitting, standing, and stepping. RESULTS:In our study population, 562 individuals were obese. 19.4% of the obese individuals and 72.7% of the non-obese individuals was metabolically healthy. After adjustments for age, sex, educational level, smoking, alcohol use, waking time, T2DM, history of CVD and mobility limitation, MHO (n = 107) spent, per day, more time stepping (118.2 versus 105.2 min; p<0.01) and less time sedentary (563.5 versus 593.0 min., p = 0.02) than MUO (n = 440). In parallel, MHNO (n = 1384) spent more time stepping (125.0 versus 115.4 min; p<0.01) and less time sedentary (553.3 versus 576.6 min., p<0.01) than MUNO (n = 518). CONCLUSION:Overall, the metabolically healthy groups were less sedentary and more physically active than the metabolically unhealthy groups. Therefore, physical activity and sedentary time may partly explain the presence of the metabolic syndrome in obese as well as non-obese individuals.